2013
DOI: 10.1371/journal.pone.0069848
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression at the Maternal-Fetal Interface in Preeclampsia Is Influenced by Gestational Age

Abstract: Genome-wide transcription data of utero-placental tissue has been used to identify altered gene expression associated with preeclampsia (PE). As many women with PE deliver preterm, there is often a difference in gestational age between PE women and healthy pregnant controls. This may pose a potential bias since gestational age has been shown to dramatically influence gene expression in utero-placental tissue. By pooling data from three genome-wide transcription studies of the maternal-fetal interface, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The top three altered PE pathway categories in the decidual transcriptome were immunity/inflammation, cell signalling and apoptosis, representing 28 altered gene sets, which were consistently altered between both transcriptome profiling batches. These pathway categories are consistent with the published literature [ 24 , 59 ]. The top pathway category of immunity/inflammation supports the growing evidence of a highly dysregulated immune and inflammatory response at the PE maternal-fetal interface [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…The top three altered PE pathway categories in the decidual transcriptome were immunity/inflammation, cell signalling and apoptosis, representing 28 altered gene sets, which were consistently altered between both transcriptome profiling batches. These pathway categories are consistent with the published literature [ 24 , 59 ]. The top pathway category of immunity/inflammation supports the growing evidence of a highly dysregulated immune and inflammatory response at the PE maternal-fetal interface [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, none of the genes in our study were reported to change expression throughout gestation based on a comparative study conducted by Winn et al [33], which compared gene expression between mid-gestation decidual tissues and term decidual tissues. A recent study, which analysed transcription profiles by merging data from different genome-wide platforms, showed that differential decidual gene expression observed in PE can be influenced by gestational age, highlighting the importance of gestational age matching between sample groups [34]. Their analyses did not show the genes examined in this study to be influenced by gestation [34].…”
Section: Discussionmentioning
confidence: 84%
“…A recent study, which analysed transcription profiles by merging data from different genome-wide platforms, showed that differential decidual gene expression observed in PE can be influenced by gestational age, highlighting the importance of gestational age matching between sample groups [34]. Their analyses did not show the genes examined in this study to be influenced by gestation [34]. All genes ACVR1 , ERAP1 , ERAP2 , LNPEP and COL4A2 differentially expressed in the large set with the exception of INHBB and COL4A1 , were also differentially expressed in the smaller subset, which was gestationally matched, suggesting gestation had no effect on our gene expression and that it is PE state that changes the gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…As the gestational age of LOSPE is more close to that of controls than EOSPE does, we overlapped the DEGs of the two subclasses compared to controls to obtain the key PE-related genes in purpose of minimizing the bias. Compared with the study by Lian et al [2013] who have evaluated the relative effect of gestational age and PE on gene expression via pooling data from three different genomewide transcription studies of the maternal-fetal interface [Winn et al, 2007[Winn et al, , 2009Loset et al, 2011], none of our 22 core regulatory genes are gestational age-associated transcripts. According to the study by Winn et al [2007], two of our 22 core regulatory genes (P4HA1 and GSTO1) are reported to change expression with gestational age, indeed they decrease toward term.…”
Section: Discussionmentioning
confidence: 99%